Flagellin From Pseudomonas aeruginosa Modulates SARS-CoV-2 Infectivity in Cystic Fibrosis Airway Epithelial Cells by Increasing TMPRSS2 Expression - Ruffin, Manon; Bigot, Jeanne; Calmel, Claire; Mercier, Julia; Givelet, Maëlle; Oliva, Justine; Pizzorno, Andrés; Rosa-Calatrava, Manuel; Corvol, Harriet; Balloy, Viviane; Terrier, Olivier; Guillot, Loïc (Frontiers in Immunology, 2021)
In the coronavirus disease 2019 (COVID-19) health crisis, one major challenge is to identify the susceptibility factors of severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) in order to adapt the recommendations for populations, as well as to reduce the risk of COVID-19 development in the most vulnerable people, especially patients with chronic respiratory diseases such as cystic fibrosis (CF). Airway epithelial cells (AECs) play a critical role in the modulation of both immune responses and COVID-19 severity. SARS-CoV-2 infects the airway through the receptor angiotensin-converting enzyme 2, and a host protease, transmembrane serine protease 2 (TMPRSS2), plays a major role in SARS-CoV-2 infectivity. Here, we show that the main component of Pseudomonas aeruginosa flagella, the protein flagellin, increases TMPRSS2 expression in AECs, particularly in patients with deficiency of the ion channel CF transmembrane conductance regulator, through activation of Toll-like receptor-5 and p38. Notably, this upregulation of TMPRSS2 expression is associated with an increased level of SARS-CoV-2 infection. Considering the urgency of the COVID-19 health crisis, this result is of major clinical significance for CF patients, who are frequently infected with and colonized by P. aeruginosa during the course of CF and might develop COVID-19.